REKRUTMEN DAN SELEKSI SUMBER DAYA MANUSIA DI ERA DIGITAL - Raflika, Lili; Putri, Rizka Amanda; Ardiansyah, M. Yasir (Cahaya Ilmu Bangsa, 2024)
This article discusses the transformation of the human resources (HR) recruitment and selection process in the digital era. Digitalization has brought significant changes in the way companies search, screen, and select candidates. The use of technologies such as artificial intelligence (AI), big data, applicant tracking systems (ATS), and video interviews increases the efficiency and effectiveness of the process. With these technologies, companies can reach candidates globally, accelerate decision-making, and optimize candidate fit with organizational needs. However, the implementation of technology also faces challenges, including the need for HR team adaptation, resistance to change, and the risk of algorithmic bias. Through a literature review, this article identifies the opportunities and constraints of implementing technology in HR management, and provides strategic insights to overcome these challenges. Artikel ini membahas transformasi proses rekrutmen dan seleksi sumber daya manusia (SDM) di era digital. Digitalisasi telah membawa perubahan signifikan dalam cara perusahaan mencari, menyaring, dan memilih kandidat. Penggunaan teknologi seperti kecerdasan buatan (AI), big data, sistem pelacakan pelamar (ATS), dan wawancara video meningkatkan efisiensi dan efektivitas proses. Dengan teknologi ini, perusahaan dapat menjangkau kandidat secara global, mempercepat pengambilan keputusan, dan mengoptimalkan kecocokan kandidat dengan kebutuhan organisasi. Namun, implementasi teknologi juga menghadapi tantangan, termasuk perlunya adaptasi tim HR, resistensi terhadap perubahan, dan risiko bias algoritma. Melalui studi literatur, artikel ini mengidentifikasi peluang dan kendala penerapan teknologi dalam manajemen SDM, serta memberikan wawasan strategis untuk mengatasi tantangan tersebut.